Museum-Based Distance Learning Programs: Current Practices and Future Research Opportunities - Ennes, Megan (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2021)
Museums play an important role in out-of-school learning. Many museums have begun offering distance learning programs to increase their reach and the accessibility of their collections. These programs serve a wide range of audiences from pre-kindergarten to lifelong learners. This descriptive study examined the current practices in museum-based distance learning programs. Additional data was collected once museums began closing due to COVID-19 and transitioning to distance learning programs. The study found that museums offering programs before COVID-19 predominately offered school-based programs via teleconferencing software. Museums transitioning to distance learning programs following closures due to COVID-19 mainly utilized social media platforms to offer a wide range of programming for the general public. Additional information was gathered regarding how the programs were developed and who facilitated them. Museums are still determining how to respond to COVID-19 closures. This study described the current landscape and potential opportunities for research related to museum-based distance learning programs. These areas for research include establishing best practices, defining high-quality programs, opportunities to engage in instructional design, and professional development for the museum staff facilitating these programs.